Associations of Dietary and Circulating Vitamin E Level With Metabolic Syndrome. A Meta-Analysis of Observational Studies - Zhang, Yi; Ding, Jun; Guo, Hongbin; Liu, Ze; Liu, Qi; Li, Yusheng; Zhang, Dianzhong; Liang, Jieyu (Frontiers in Nutrition, 2021)
Objective: The associations of dietary and circulating vitamin E level with metabolic syndrome (MetS) remains conflicting. This meta-analysis of observational study was therefore employed to further investigate the issue above. Methods: The PubMed, Web of Science and Embase database were searched up to April 2021, for observational studies on the associations of dietary and circulating vitamin E level with MetS. The pooled relative risk (RR) of MetS for the highest versus lowest dietary and circulating vitamin E level, and the standard mean difference (SMD) of dietary and circulating vitamin E level for MetS versus control subjects, were calculated. Results: A total of 25 observational studies with 51276 participants, were included in this meta-analysis. The overall multi-variable adjusted RR demonstrated that dietary vitamin E level was inversely associated with MetS (RR=0.92, 95%CI: 0.85 to 1.00; P=0.044). In addition, the dietary vitamin E level in MetS was lower than that in control subjects according to the overall combined SMD (SMD=-0.08, 95%CI: -0.14 to -0.02; P=0.024). On the other hand, the overall multi-variable adjusted RR showed no significant relationship between circulating vitamin E level and MetS (RR=1.46, 95%CI: 0.85 to 2.48; P=0.17). However, the circulating vitamin E level in MetS was lower than that in control subjects according to the overall combined SMD (SMD=-0.58, 95%CI: -1.04 to -0.13; P=0.013). Conclusions: The results of this meta-analysis suggest that the dietary vitamin E level is inversely associated with MetS, However, current evidence is still insufficient to conclude a definite relationship between the circulating vitamin E level and MetS. More well-designed studies are needed to address the issues further.